Development of an analytical solution for the parallel second order reaction scheme for chlorine decay modelling - Jabari Kohpaei, Ahmad (Curtin University, 2010)
Chlorine is broadly used for water disinfection at the final stage of water treatment because of its high performance to inactivate pathogenic microorganisms, its lower cost compared to other well-known disinfectants and its simple operational needs. However, reaction of chlorine with a wide range of organic and inorganic substances in water causes its decay and formation of chlorinated by-products, which are in some cases carcinogenic and harmful to human health. The major challenge is balancing the risk from these with the cost of operation needed to mitigate the impact. These challenges highlights the importance of having a robust modelling approach for chlorine decay in bulk water as a pre-required step to model the chlorine decay and formation of its by-products in the whole distribution system.In this study, initially, a comprehensive literature review was conducted to investigate and evaluate all existing modelling approaches for chlorine decay prediction especially in bulk water. Among all existing modelling schemes, three models were paid more attention due to their popularity and/or fundamentally valid background. They are first order model, second order model and parallel second order model.During the literature review, comparing the effectiveness of the second order model (SOM) proposed by Clark (1998) with the parallel second order model (PSOM) offered by Kastl et al., (1999), the author found that these two models are both fundamentally sound, although the PSOM had better capability in terms of data fitting, and representing the chlorine decay behaviour is much better than SOM. However, non-existence of analytical solution for PSOM was found to be the major negative point for wide adaptation of PSOM compared to SOM.Trying to understand the basic principles of both models, it was understood that the formulation of SOM was genuine and the researchers who claimed that Clark (1998) made a mistake in deriving the analytical solution were proved wrong. This resulted in having the first publication as a comment in Water Research (Fisher et al., 2010b; Appendix A3).Further study was performed on how SOM was formulated and attempts were made to apply the same methodology to PSOM in order to arrive at an analytical solution. Consequently, making a reasonable assumption, an analytical solution for the parallel second order model was formulated and evaluated against the existing numerical method.As the case study of this research, initially, the previous chlorine decay data from Pilbara Water Treatment Plant was fitted to a first order reaction scheme and it was proved that the data did not comply with it. This was an expected result and the need for other model was validated. For further analysis, fresh water samples were collected from Pilbara Water Treatment Plant to perform chlorine decay tests.Temperature effect on the behaviour of chlorine decay in the bulk water was investigated by integrating Arrhenius equation with PSOM. Three methods of temperature analysis were compared and the best one was recommended for practical application. It was shown that the model was capable enough to properly display the chlorine decay profile when temperature varies.The thesis consists of eight chapters. In chapter 1, a brief description of the research background and the overall objectives of the research are given. Chapter 2 focuses on providing a comprehensive literature review about all involved aspects as well as chlorine decay modelling background. Chapter 3 discusses the methodology and analytical methods for conducting laboratory experiments. Chapter 4 gives a prove that the first order decay model does not show accurate results for chlorine decay prediction and the parallel second order model is much more accurate in predicting chlorine concentration. In Chapter 5, the main part of this research, an analytical solution for the parallel second order model is developed. Chapter 6 evaluates the effectiveness of the parallel second order model against the first and second order model. Within chapter 7, temperature effect on the chlorine decay behaviour and the selected modelling approach is evaluated and chapter 8 gives a brief conclusion and recommendation.